2019
DOI: 10.1108/edi-02-2019-0084
|View full text |Cite
|
Sign up to set email alerts
|

Women directors and performance: evidence from Malaysia

Abstract: Purpose The purpose of this paper is to examine the relationship between women on board and the financial performance of Malaysian listed companies. Design/methodology/approach Panel generalised method of moments (GMM) analysis was used over 928 public-listed companies listed on the Malaysian Stock Exchange from 2010 to 2016. GMM overcomes the problem of endogeneity and simultaneity bias. The dependent variable was firm performance, measured by Tobin’s Q. The explanatory variable was gender diversity, proxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 53 publications
4
49
3
Order By: Relevance
“…Studies in the Malaysian context also established mixed findings. Julizaerma and Sori (2012) and Lee-Kuen et al (2017) found a positive influence of gender diversity on Malaysian firms’ financial performance, whereas Abdullah (2014) and Lim et al (2019) indicated that gender diversity had an adverse influence on the financial performance. Meanwhile, studies in the Indonesian context are limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies in the Malaysian context also established mixed findings. Julizaerma and Sori (2012) and Lee-Kuen et al (2017) found a positive influence of gender diversity on Malaysian firms’ financial performance, whereas Abdullah (2014) and Lim et al (2019) indicated that gender diversity had an adverse influence on the financial performance. Meanwhile, studies in the Indonesian context are limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to research conducted by Kanter in 1977, if there is only one female director on the Board, this person will hardly change the company's decisions, if the number is two, then these directors will only influence on voting of opinion, however, only when the number of females is three or more, female directors will affect the decision-making process. This theory is again proved by Kristie (2011) and Lim et al (2019), if the number of women is by far minority (1 or 2) in the Board of Directors, there will be pressure on gender and decisions based on the majority (here is male managers). Similarly, when the CEO is female, making the company's decisions becomes more difficult, requiring a large number of members of the Board of Directors; while the CEO is male, the decisions-making are often better so that the number of members of the Board of Directors does not require a large quantity.…”
Section: H2: Number Of Times To Replace Ceo Is Negatively Related To mentioning
confidence: 85%
“…While there is a growing body of research on the effect of board gender diversity on firm performance, existing empirical evidences remain ambiguous and have yielded conflicting results. Some studies provided support for women's presence on the board (Ahmadi et al , 2018; Arun et al , 2015; Kim and Starks, 2016; Liu et al , 2014; Nguyen et al , 2015; Reguera-Alvarado et al , 2017), whereas other studies found no link between board gender diversity and firm performance (Carter et al , 2010; Ciftci et al , 2019; Dimovski and Brooks, 2006; Marinova et al , 2016; Miller and del Carmen Triana, 2009) and at times, a negative relationship (Adams and Ferreira, 2009; Ahern and Dittmar, 2012; Lim et al , 2019; Terjesen et al , 2016). The mixed results of past studies could be due to the data from different contexts, time periods or measures of firm performance (Johnson et al , 2013; Li and Chen, 2018; Pletzer et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one literature stream, opponents of board diversity argue that gender diversity is unrelated to firm performance, or some suggest that board diversity exhibits negative impact on firm performance (Erhardt et al , 2003; Lamers, 2016; Petrovic, 2008; Smith et al , 2006). Lim et al (2019) and Lamers (2016) argued that board diversity results in conflicts that negatively affect firm performance. These conflicts might stem from lack of sufficient solidarity and conformity (Pelled et al , 1999), which leads to more time-consuming decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation